Revitalisation Design of North Coastal Border in Lemahwungkuk Sub-District with Urban Design Element Analysis - Fauzi, Difa Farhan; Yudhistira A. F, Iqra; Budisiswanto, Nurulllah; Oktaria S K, Dinar (Riviera Publishing, 2024)
Cirebon is one of the cities in West Java province. The city is located in the lowlands on the north coast of Java. The low topography factor is closely related to urban problems, such as slums in the Lemahwungkuk sub-district of Cirebon City. This research aims to solve urban problems because, according to the Mayor's Regulation No. 663/Kep.421-DPRKP/2021, Lemahwungkuk sub-district includes Cangkol coastal and Kesunean coastal areas among the eleven slum locations in Cirebon city. In addition, there is a plan to revitalize the coastal border area. The method used in this research is qualitative, using urban design analysis and site analysis. The data sources were obtained through interviews with 20 informants and mapping using ArcGIS 10.8 software. The concept of an environmental approach with an orientation towards the community in the design of the revitalization of the north coast area in Lemahwungkuk District emphasizes the physical environment, infrastructure, economy, socio-culture, disaster, and collaboration between the government and the community. The results of this revitalization design can also be a recommendation for development in Cirebon, West Java. In addition, it recommends conservation and tourism activities on the north coast of Cirebon, West Java. Efforts to overcome the phenomenon of urban sprawl at the research site by changing the pattern of settlements and building layout to improve the quality of the community environment and increase public space and green open space for conservation, tourism, and aesthetic functions of the region.